Trajetórias de acumulação de capacidades inovadoras, mecanismos de aprendizagem e fatores organizacionais relativos a atividades em gestão de projetos: estudo de caso comparativo inter-empresarial na indústria de bens de capital e de celulose e papel no Brasil - Fröhard, Jaime Andrés Castro (2009)
Over the last 40 years there has been a profusion of studies about the ccumulation of technological capacities in firms from developing economies. However, there remain few studies that examine, on a combined basis, the relationship among: the trajectories of technological capacities accumulation; the underlying learning mechanisms; and, the implications of organizational factors for these two variables. Still scarcer are the studies that examine the relationship among these variables along time and based on a comparative case study. This dissertation examines the relationship among the trajectory of accumulation of innovative capacities in complex project management, the learning mechanisms underlying these technological capacities and the intra-organizational factors that influence these learning echanisms. That set of relationships is examined through a comparative and a long-term (1988-2008) case study in a capital goods firm (for the pulp and paper industry) and a pulp mill in Brazil. Based on first-hand quantitative and qualitative empiric evidence, gathered through extensive field research, this dissertation found: 1. Both firms accumulated innovative capacity in project management at the international frontier level (Level 6). However, there was variability between the firms in terms of the nature and speed of accumulation of those capacities. It was also observed that, at this level of innovation, the innovative capacities of both firms are not confined to their organizational boundaries, but they are distributed beyond their boundaries. 2. So that these companies could accumulate those levels of innovative capacities it was necessary to manage several learning mechanisms: leveraging of external knowledge and its internalization in terms of internal apacities of the firm. In other words, as the companies accumulated more innovative levels of capacities for project management, it was necessary to manage different cycles of technological learning. 3. Further, the relationship between the ccumulation of technological capacities and learning was affected positively by intra-organizational factors, such as 'authority disposition', 'mutability of work roles' and 'intensity of internal crises', and negatively by the factor 'singularity of goals'. This dissertation revealed divergent results between firms in two of the four factors studied. These results contribute to advance our understanding of the complexity and variability involved in the process of accumulation of innovative capacities in firms from developing economies. This highlights the growing importance of the organizational and the human resource dimensions of innovation and technological capacity as the company approaches the international frontier. The results suggest to managers that: (i) the good performance in project management in the two firms studied did not occur simply as a result of the pulp and paper Brazilian industry growth, rather as a result of the deliberate construction and accumulation of the capacities through an intensive and coordinated cyclical process of technological learning, (ii) to develop innovative capabilities in project management, besides looking for learning mechanisms they should also look at the organizational factors that influence the learning mechanisms directly, (iii) performance of pulp mill¿s projects is better when projects are implemented together with technology suppliers than when performed only by the mill. This dissertation concludes that capital goods firms have been having a fundamental role for the innovative capabilities accumulation in project management of pulp mills in Brazil (and vice-versa) for a long time. This contradicts some authors' propositions that affirm that: a) equipment suppliers for the pulp and paper industry have been creating little, if any, development of processes or engineering projects in Brazil; b) firms in the pulp and paper industry have little capacity for machinery and equipments projects only taking place in few technological activities, being internal or external to the firm. Finally, some studies are proposed for future research.